2018
DOI: 10.1002/2017ja024718
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Tidal Modulation of Periodic Meridional Movement of Equatorial Ionization Anomaly Crest During Sudden Stratospheric Warming

Abstract: Using the location of equatorial ionization anomaly (EIA) crest derived from GPS observations in China and Brazilian sector, we investigated the longitudinal dependence of periodic meridional movement of EIA crest during sudden stratospheric warming events in 2003, 2006, and 2009. The solar activity was from high to low for the three events. Results show that the locations of EIA crests in both China and Brazilian sectors exhibit obvious and constant 14‐ to 15‐day periodic oscillation being in‐phase in two sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 48 publications
(104 reference statements)
3
33
0
Order By: Relevance
“…Note that quasi 10-day oscillations of northern and southern EIA crests are in-phase, which are consistent with quasi 16-day oscillations in northern and southern EIA crests during 2002-2003 NH SSW, suggesting quasi 10-day oscillations of northern and southern EIA crests are caused by common physical processes, e.g. fountain effect (Mo et al, 2018).…”
Section: Results and Analysissupporting
confidence: 72%
“…Note that quasi 10-day oscillations of northern and southern EIA crests are in-phase, which are consistent with quasi 16-day oscillations in northern and southern EIA crests during 2002-2003 NH SSW, suggesting quasi 10-day oscillations of northern and southern EIA crests are caused by common physical processes, e.g. fountain effect (Mo et al, 2018).…”
Section: Results and Analysissupporting
confidence: 72%
“…It has been demonstrated that the ionosphere could be remarkably disturbed during SSW events, and one of the most distinct responses is the occurrence of a semidiurnal pattern in ionospheric parameters (Anderson & Araujo-Pradere, 2010;Chau et al, 2009;Chau et al, 2012;Fang et al, 2012;Fang et al, 2014;Fejer et al, 2010;Fuller-Rowell et al, 2011;Goncharenko et al, 2012;Goncharenko & Zhang, 2008;He et al, 2017;Maute et al, 2015;Mo & Zhang, 2018;Pedatella et al, 2012;Pedatella & Forbes, 2009;Pedatella & Forbes, 2010;Siddiqui et al, 2017). It is first shown in Goncharenko and Zhang (2008) with the analysis of ion temperature from the Millstone Hill Incoherent Scatter Radar.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, a 14-to-15 d wave during several NH SSW events is ascribed to lunar tide (Mo et al, 2018). So the source of quasi-10 d oscillations in the EIA region during the 2002 SH SSW is different from 14-to-15 d waves during the NH SSW.…”
Section: Discussionmentioning
confidence: 84%
“…1. Since the ionospheric vertical TEC usually reaches the maximum at the EIA crest, the location of the EIA crest can be obtained by vertical TEC values at each ionospheric penetration point (IPP), which is the intersection of the line of sight and the ionospheric shell (assumed to be 400 km) (Mo et al, 2014). The relative accuracy of the TEC is 0.02 total electron content units (1 TECU = 10 16 electrons m −2 ) (Hofmann-Wellenhof et al, 1992).…”
Section: Introductionmentioning
confidence: 99%